Left Bank of the Hudson : Jersey City and the Artists of 111 1st Street. - Goodwin, David J. (Fordham University Press, 2017)
"For nearly twenty years, a small, dedicated band of artists rented studio space at 111 1st Street, a former tobacco warehouse near the Hudson River waterfront in Jersey City, New Jersey. These artists eventually became engaged in a fight for their survival within the building and a city undergoing gentrification"--